Flow-enhanced priming of hESCs through H2B acetylation and chromatin decondensation - Wang, Jiawen (Stem Cell Res Ther, 2019)
BACKGROUND: Distinct mechanical stimuli are known to manipulate the behaviors of embryonic stem cells (ESCs). Fundamental rationale of how ESCs respond to mechanical forces and the potential biological effects remain elusive. Here we conducted the mechanobiological study for hESCs upon mechanomics analysis to unravel typical mechanosensitive processes on hESC-specific fluid shear. METHODS: hESC line H1 was subjected to systematically varied shear flow, and mechanosensitive proteins were obtained by mass spectrometry (MS) analysis. Then, function enrichment analysis was performed to identify the enriched gene sets. Under a steady shear flow of 1.1 Pa for 24 h, protein expressions were further detected using western blotting (WB), quantitative real-time PCR (qPCR), and immunofluorescence (IF) staining. Meanwhile, the cells were treated with 200 nM trichostatin (TSA) for 1 h as positive control to test chromatin decondensation. Actin, DNA, and RNA were then visualized with TRITC-labeled phalloidin, Hoechst 33342, and SYTO® RNASelect™ green fluorescent cell stain (Life Technologies), respectively. In addition, cell stiffness was determined with atomic force microscopy (AFM) and annexin V-PE was used to determine the apoptosis with a flow cytometer (FCM). RESULTS: Typical mechanosensitive proteins were unraveled upon mechanomics analysis under fluid shear related to hESCs in vivo. Functional analyses revealed significant alterations in histone acetylation, nuclear size, and cytoskeleton for hESC under shear flow. Shear flow was able to induce H2B acetylation and nuclear spreading by CFL2/F-actin cytoskeletal reorganization. The resulting chromatin decondensation and a larger nucleus readily accommodate signaling molecules and transcription factors. CONCLUSIONS: Shear flow regulated chromatin dynamics in hESCs via cytoskeleton and nucleus alterations and consolidated their primed state.